Are the U.S. Navy's current procedures for responding to homeland defense and security tasking adequately designed? - McClellan, Kevin K. (Monterey, California. Naval Postgraduate School, 2009)
With the spectrum of the range of military operations broadening, the operational tempo of Department of Defense assets has substantially increased. Military leaders must look to innovative solutions to meet the increased demands placed on the armed forces. Doctrine and policy such as the National Security Strategy, National Military Strategy and the Strategy for Homeland Defense and Civil Support dictate the increased use of innovation and "jointness" by the military in order to meet the increasing demands of protecting the homeland. The question, "Are the U.S. Navy's current procedures for responding to homeland defense and security tasking adequately designed?" needs to be addressed to ensure our nation is fulfilling its most essential duty: providing safety and security for its citizens. This thesis will discuss the establishment of NORTHCOM, analyze and detail the potential mission set the U.S. Navy can execute in homeland defense and security and examine the current command and control (C2) relationships that NORTHCOM has with the U.S. Navy compared to the other military services. The thesis will then provide alternate C2 options between NORTHCOM and the U.S. Navy as well as identify the advantages and disadvantages of those options and conclude with an analysis and recommendations. Approved for public release; distribution is unlimited. http://archive.org/details/areusnavyscurren1094510413